Peningkatan Pemahaman Konsep dan Hasil Belajar Siswa Menggunakan Media Kantong Bilangan pada Materi Nilai Tempat di Kelas 2 SDN 2 Ampenan - Parizka, Nindy Nursilva; Suwasa Astawa , I Made; Khaer, Fikratul (Mataram University, 2025)
The low learning outcomes of students in mathematics are caused by the teacher’s inability to create an engaging learning process. This Classroom Action Research (CAR) aims to examine whether the use of number pocket media can improve students’ conceptual understanding of place value material. The research was conducted in two cycles, each consisting of four stages: planning, implementation, observation, and reflection. The subjects of this study were 21 second-grade students at SDN 2 Ampenan. Data were collected through tests and observation sheets, and analyzed both quantitatively and qualitatively. The results showed a significant improvement in students’ understanding of the place value concept, which directly impacted their learning outcomes. The average score of students’ conceptual understanding increased from 68.25 in the first cycle to 82.86 in the second cycle, while the average learning outcome rose from 70.37 in the first cycle to 85.24 in the second cycle, with a mastery level reaching 85.7%. This improvement demonstrates that the use of number pocket media is effective in helping students better understand the concept of place value, thereby enhancing their overall learning achievement.